Preparation and Modification of Silicalite-2 Membranes - Yin Yang; Juan Liu; Qi Zhou; Siqi Shao; Lingling Zou; Wenjun Yuan; Meihua Zhu; Xiangshu Chen; Hidetoshi Kita (Membranes)
Silicalite-2 membranes were successfully prepared on tubular α-Al2O3 supports by secondary hydrothermal synthesis, and the pervaporation performance of the membrane was evaluated by separation of a 5 wt% ethanol/H2O mixture at 60 °C. The effects of templating agent content, water–silicon ratio and crystallization time on the separation performance of Silicalite-2 membranes were investigated. When the TBAOH/SiO2 and H2O/SiO2 molar ratios of the precursor synthesis solution were 0.2 and 120, a dense Silicalite-2 membrane could be prepared on the surface of the tubular α-Al2O3 support after 72 h. The silane coupling agent was utilized to treat the Silicalite-2 membranes, and the effects of silane coupling agent dosage on their properties were also explored. The pervaporation performance of the Silicalite-2 membrane was greatly improved with a 5.7 wt% trimethylchlorosilane (TMCS) solution and the flux and separation factor of the membrane reached 1.75 kg·m−2·h−1 and 22 for separation of 5 wt% EtOH/H2O at 60 °C, respectively.